'They've always been there for me': grandparental involvement and child well-being - Griggs, Julia; Tan, Jo Pei; Buchanan, Ann; Attar-Schwartz, Shalhevet; Flouri, Eirini (National Children's Bureau, 2010)
With diversifying families, increased life expectancy, growing numbers of dual-worker households and higher rates of family breakdown, grandparents are now playing an increasing role in their grandchildren’s lives. Despite growing importance there has been little empirical research exploring how grandparental involvement impacts on young people’s well-being. This national study, which includes a survey of 1596 children (aged 11—16) and in-depth interviews with 40 young people, aimed to address this deficit. Multivariate analyses demonstrate that grandparental involvement is significantly associated with child well-being — results that are reinforced by qualitative evidence. Findings suggest grandparents may be under-recognised in the policy agenda.